2019
DOI: 10.1371/journal.pone.0216131
|View full text |Cite
|
Sign up to set email alerts
|

Identifying anomalous nuclear radioactive sources using Poisson kriging and mobile sensor networks

Abstract: Nuclear security is a critical concept for public health, counter-terrorism efforts, and national security. Nuclear radioactive materials should be monitored and secured in near real-time to reduce potential danger of malicious usage. However, several challenges have arose to detect the anomalous radioactive source in a large geographical area. Radiation naturally occurs in the environment. Therefore, a non-zero level of radiation will always exist with or without an anomalous radioactive source present. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…N. Rao et al (Rao et al, 2015) suggested a Particle Filter algorithm, where it has been used in a border monitoring scenario. A geostatistical interpolation method that uses the given measurements to estimate positions where data were not collected based on Poisson kriging is presented (Zhao et al, 2019). Fragkos et al (2020) developed a fusion algorithm based on an analytical procedure for five sensors.…”
Section: Introductionmentioning
confidence: 99%
“…N. Rao et al (Rao et al, 2015) suggested a Particle Filter algorithm, where it has been used in a border monitoring scenario. A geostatistical interpolation method that uses the given measurements to estimate positions where data were not collected based on Poisson kriging is presented (Zhao et al, 2019). Fragkos et al (2020) developed a fusion algorithm based on an analytical procedure for five sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The search of radioactive sources using mobile sensor networks was proposed in References [ 91 , 92 ], using Poisson Krigin techniques for the spatial distribution of radiation levels and source location, and in Reference [ 93 ], adopting a Bayesian framework and a sequential Monte Carlo for parameters estimation.…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…In few recent decades the issues of radiation safety are becoming increasingly important. This is caused by the various reasons [2] including essential increasing the nuclear waste, expansion of the areas of contaminated land, intensive use of nuclear materials in military [3] and civilian purposes, operation of power plants containing the nuclear reactors (nuclear plants, submarines, 1049 (2022) 012015 IOP Publishing doi:10.1088/1755-1315/1049/1/012015 2 missiles, and etc. ), increasing a number of terrorist attacks and level of their preparation.…”
Section: Introductionmentioning
confidence: 99%
“…• in contrast to the manned vehicles, UAVs do not require special strict regulations or permissions, there are less problem with pilot's safety; • UAVs can provide more detail explorations of the areas with complicated reliefs or obstacles [2,12,13]; • their exploitation is less expensive;…”
Section: Introductionmentioning
confidence: 99%